Revisiting the issue of gender - Ahmad, Shahbaz (South Asian Journal of Socio-Political Studies)
Discussion on the issue of gender ultimately boils down to a demand for equality of men and women in all respects. The psycho-social realities and the findings in the field of neurology, psychology and sociology are ignored to a large extent. As a consequence, the corollaries of all deliberations on gender issue are often misleading. The male value system is propagated and the female value system is disregarded. It is found that most of the countries excelling in gender equality are also facing the problems of family breakdown, offences against women and neglect of children. It is so because the deliberations on gender often acquire an emotional tinge to avoid the real psycho-social issues. It is time to rethink and visit afresh the issue of gender in a pragmatic manner.- Reproduced